Perancangan Sistem Informasi Aplikasi Tracer Study Alumni Berbasis Website - Rizal Bagus Pambudi; Agung Triayudi; Andrianingsih Andrianingsih (STMIK Budi Darma, 2020)
Tracer Study is a study conducted by tertiary institutions to search for alumni whose purpose is to find out the reciprocal of alumni education in the world of work. National universities themselves already have a tracer study website but still have difficulty in carrying out tracer studies, especially to contact alumni. The method used in this study uses a structured waterfall method. In this case, the initial stage for this method is to make observations that aim to find and find out the problems faced by users and to collect data by searching literature studies related to website-based tracer studies to testing website testing systems using blackboxes, namely testing the function requirements of each menu in a program. This research resulted in the application of a website-based tracer study system that facilitates alumni to carry out the tracer study process which can be done anytime and anywhere. The results of the tracer study itself will serve as a benchmark for the university in developing the ability of future students to compete in the workforce.